ICT Based Chemistry Learning Innovation To Improve Student's Creativity In The Digital Era - Ratna Kumala Dewi; Nur Kholis; Siti Marpuah; Mohammad Ghozali; Syahrudin (Journal of Social Transformation and Regional Development, 2022)
Information, Communication, and Technology (ICT) continue to develop in the digital era. In this digital era, all data will obtained easily online. The development of learning media can be applied in the presence of ICT. One of the subjects that can use ICT as a medium is chemistry. This study aimed to describe the role of ICT in chemistry learning to increase students' creativity. Methods of data collection are done by documentation and literature study. Data sources are obtained from references to research results, journal articles, and other related sources. The form of ICT development in the field of conventional to modern chemistry education is with chemistry e-modules, virtual laboratory applications with (Phet), applications for drawing chemical structures online with ChemDraw, Chem3D, Jmoll, Chem and Sketch, as well as making chemical animation videos with PowerPoint, Fillmora, Powtoon, Flash, etc. Based on the results and discussion, it can conclude that ICT innovation in the chemistry learning system could increase students' creativity in the digital era.